2019
DOI: 10.2196/12373
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Patients’ Use of Electronic Personal Health Records in England: Cross-Sectional Study

Abstract: BackgroundElectronic personal health records (ePHRs) are secure Web-based tools that enable individuals to access, manage, and share their medical records. England recently introduced a nationwide ePHR called Patient Online. As with ePHRs in other countries, adoption rates of Patient Online remain low. Understanding factors affecting patients’ ePHR use is important to increase adoption rates and improve the implementation success of ePHRs.ObjectiveThis study aimed to examine factors associated with patients’ u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 72 publications
7
50
1
Order By: Relevance
“…Privacy and security concerns were found to have a significant negative effect on behavioral intention to use standalone ePHR systems by adults in Egypt, this result came in consistency with several studies in literature (Pottas & Mostert-phipps, 2013;Abdekhoda et al, 2019 ;Abd-Alrazaq et al, 2019b ), the result in this research was contradicting with other studies from literature (Cocosila & Archer, 2014;Al-Sahan & Saddik, 2016) which found insignificant effect of privacy and security concerns on behavioral intention, the result indicated a small direct effect of privacy and security concerns on behavioral intention which means that privacy and security concerns are representing a barrier for standalone ePHR adoption but without a major impact, however it should be handled with care to overcome its negative effect on behavioral intention.…”
Section: Hypotheses Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…Privacy and security concerns were found to have a significant negative effect on behavioral intention to use standalone ePHR systems by adults in Egypt, this result came in consistency with several studies in literature (Pottas & Mostert-phipps, 2013;Abdekhoda et al, 2019 ;Abd-Alrazaq et al, 2019b ), the result in this research was contradicting with other studies from literature (Cocosila & Archer, 2014;Al-Sahan & Saddik, 2016) which found insignificant effect of privacy and security concerns on behavioral intention, the result indicated a small direct effect of privacy and security concerns on behavioral intention which means that privacy and security concerns are representing a barrier for standalone ePHR adoption but without a major impact, however it should be handled with care to overcome its negative effect on behavioral intention.…”
Section: Hypotheses Testingsupporting
confidence: 89%
“…Perceived usefulness was found to have a significant positive effect on behavioral intention to use standalone ePHR systems by adults in Egypt and it was one of the strongest predictors in the model, this result came in consistency with other researchers from different contexts worldwide (Noblin et al, 2013;Cocosila & Archer, 2014;Yuan et al, 2015;Tavares and Oliveira, 2016;Alhammad, 2017;Hsieh et al, 2017;Dutta et al, 2018;Abd-Alrazaq et al, 2019b), this result assures the importance of perceived usefulness as a predictor of behavioral intention in the consumer health informatics context. The result also came contradicting with other studies (Chun & Hong, 2015;Koivumäki et al, 2017), they found perceived usefulness has insignificant effect on behavioral intention to adopt ePHR systems by younger adults but the situation in Egypt was different since the sample in this research had more than 75% of respondents ranging from 18 to 40 years old.…”
Section: Hypotheses Testingsupporting
confidence: 87%
“…The hack attacks that happened to the NHS 4 months before data collection may have exacerbated these concerns in this sample. This finding is consistent with the results of the quantitative data in the original study [ 27 ], where perceived privacy and security significantly affected patients’ intention to use Patient Online. This factor was also found in other quantitative studies [ 33 - 36 ] and qualitative studies [ 37 - 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…The qualitative data provide the focus of this study. Note that the findings from the quantitative analysis of the survey data were presented in a previous paper [ 27 ]. The survey gained health research authority approval before starting data collection (The Research Ethics Committee reference number: 17/SC/0323).…”
Section: Methodsmentioning
confidence: 97%
“…Consequently, developers of eHealth interventions should take the skill level and preferences of patients into account to prevent a mismatch between the technology and patient. Such a mismatch might result in high levels of non-adherence (Abd-Alrazaq et al, 2019). On the one hand, it can be beneficial to further investigate how patients can be better supported in using these mostly text-based apps or websites, which are used a great deal in current practice.…”
Section: The Patientmentioning
confidence: 99%